Effects of different exercise interventions on executive function in children with autism spectrum disorder: a network meta-analysis - Hou, Yaoqi; Wang, Yan; Deng, Jiaqi; Song, Xiangqin (Frontiers in Psychiatry, 2024)
Background: A large body of research has identified the positive effects of physical activity on children with autism spectrum disorders (ASD). However, the specific benefits of different types of sports on executive functioning in children with ASD remain unclear. The aim of this study was to further analyze the effects of different sports on executive functioning in children with ASD using reticulated meta-analysis and to establish their effectiveness ranking.Methods: This study conducted a comprehensive online search in Web of Science, PubMed, Cochrane, Embase, and CNKI databases. It included randomized controlled trials and quasi-experimental studies, and synthesized the data using a Bayesian framework.Results: Several relevant studies were included. The results showed that physical activity significantly improved all three dimensions of executive functioning (inhibitory control, cognitive flexibility, and working memory) in children with ASD. The improvement in cognitive flexibility and inhibitory control both reached a medium effect size. However, the improvement in inhibitory control was better than that in cognitive flexibility, while the improvement in working memory did not reach the level of a medium effect.